Sense of agency: Examining awareness of the acting self - Sukhvinder Obhi (Frontiers Research Topics, 2015)
The sense of agency is defined as the sense of oneself as the agent of one's own actions. This also allows oneself to feel distinct from others, and contributes to the subjective phenomenon of self-consciousness (Gallagher, 2000). Distinguishing oneself from others is arguably one of the most important functions of the human brain. Even minor impairments in this ability profoundly affect the individual's functioning in society as demonstrated by psychiatric and neurological syndromes involving agency disturbances (Della Sala et al., 1991; Franck et al., 2001; Frith, 2005; Sirigu et al., 1999). But the sense of agency also plays a role for cultural and religious phenomena such as voodoo, superstition and gambling, in which individuals experience subjective control over objectively uncontrollable entities (Wegner, 2003). Furthermore, it plays into ethical and law questions concerning responsibility and guilt. For these reasons a better understanding of the sense of agency has been important for neuroscientists, clinicians, philosophers of mind and the general society alike. Significant progress has been made in this regard. For example, philosophical scrutiny has helped establish the conceptual boundaries of the sense of agency (Bayne, 2011; Gallagher, 2000, 2012; Pacherie 2008; Synofzik et al., 2008) and scientific investigations have shed light on the neurocognitive basis of sense of agency including the brain regions supporting sense of agency (Chambon et al., 2013; David et al., 2007; Farrer et al., 2003, 2008; Spengler et al., 2009; Tsakiris et al., 2010; Yomogida et al., 2010). Despite this progress there remain a number of outstanding questions such as: • Are there cross-cultural differences in the sense of agency? • How does the sense of agency develop in infants or change across the lifespan? • How does social context influence sense of agency? • What neural networks support sense of agency (i.e., connectivity and communication between brain regions)? • What are the temporal dynamics with respect to neural processes underlying the sense of agency (i.e. the what and when of agency processing)? • How can different cue models of the sense of agency be further specified and empirically supported, especially with regards to cue integration/ weighting? • What are the applications of sense of agency research (clinically, engineering etc.)? The concept of the sense of agency offers intriguing avenues for knowledge transfer across disciplines and interdisciplinary empirical approaches, especially in addressing the afore-mentioned outstanding questions. The aim of the present research topic is to promote and facilitate such interdisciplinarity for a better understanding of why and how we typically experience our own actions so naturally and undoubtedly as "ours" and what goes awry when we do not. We, thus, welcome contributions from, for example, (i) neuroscience and psychology (including development psychology/ neuroscience), (ii) psychiatry and neurology, (iii) philosophy, (iv) robotics, and (v) computational modeling. In addition to empirical or scientific studies of the sense of agency, we also encourage theoretical contributions including reviews, models, and opinions.